Penerapan Corporate Social Responsibility pada Media Sosial: Studi Kasus Program Corporate Social Responsibility “Klik Hati” PT Merck Indonesia - Faridha Rahmaningsih (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
The aim of the research is to analyse the application of corporate social responsibility on social media in PT Merck Indonesia. Usage of social media in corporate social responsibility activities allows the creation of an interactive dialogue that is horizontal between the company and stakeholder. The research uses qualitative research methods with a case study approach. The author uses research design ‘holistic single case’. This research uses three sources of evidence including interview, document analysis, and literature review.